Beyond irreversible pulpitis: Redefining vital pulp therapy through a tissue-response-based paradigm - Asgary, Saeed (Edelweiss Applied Science and Technology, 2025)
For decades, diagnosing irreversible pulpitis (IP) has driven routine root canal treatments, despite increasing evidence that inflamed vital pulps still possess significant regenerative capacity. This review integrates epidemiological, clinical, and biological data to establish a tissue-response model centered on pulp viability and healing potential. Symptom-based diagnosis often misclassifies cases, leading to overtreatment; therefore, the traditional binary terminology (reversible vs. irreversible) should be replaced with a spectrum-based classification (mild, moderate, severe pulpitis), necessitating an urgent update of endodontic guidelines. Histological studies confirm that pulp healing can occur despite inflammation, while high-quality evidence from randomized controlled trials demonstrates the success of vital pulp therapy (VPT), achieving high success rates in teeth previously labeled as having IP. Calcium silicate-based biomaterials (e.g., MTA, CEM cement, Biodentine) support angiogenesis and regeneration of the dentin-pulp complex even in severely inflamed pulps. Factors predicting treatment success include the degree of pulpal inflammation, the type of final restoration, and the presence of apical periodontitis before treatment. By combining insights from biomaterial science, regenerative biology, and clinical trials, this review advocates a tissue-response model that emphasizes pulp healing capacity over static histological labels. This change promotes VPT as the primary treatment for inflamed pulps, prompts an immediate revision of endodontic terminology and guidelines, and establishes a regenerative, minimally invasive approach as the standard for modern endodontic care. Nevertheless, current limitations—including diagnostic uncertainty, lack of standardized protocols, and limited high-level evidence—highlight the need for further refinement before universal adoption.